Characterization of the radiation environment at the UNLV accelerator facility during operation of the Varian M6 linac. (October 2016) - Hodges, M.; Barzilov, A.; Chen, Y.; Lowe, D.
Abstract: The bremsstrahlung photon flux from the UNLV particle accelerator (Varian M6 model) was determined using MCNP5 code for 3 MeV and 6 MeV incident electrons. Human biological equivalent dose rates due to accelerator operation were evaluated using the photon flux with the flux-to-dose conversion factors. Dose rates were computed for the accelerator facility for M6 linac use under different operating conditions. The results showed that the use of collimators and linac internal shielding significantly reduced the dose rates throughout the facility. It was shown that the walls of the facility, in addition to the earthen berm enveloping the building, provide equivalent shielding to reduce dose rates outside to below the 2 mrem/h limit. Highlights: A 3/6 MeV electron accelerator equipped with a high energy x-ray target was studied. Monte Carlo modeling of photon flux was carried out for three accelerator configurations. Human biological equivalent doses were evaluated within the accelerator facility building.